Symptomatic malignant pericardial effusion due to advanced pericardial malignancies: a palliative approach - Khalid, Nauman; Chhabra, Lovely; Ahmad, Sarah Aftab; Spodick, David H. (Journal of Thoracic Disease; Vol 7, No 4 (April 28, 2015): Journal of Thoracic Disease, 2015)
We read with great pleasure the manuscript by Gong et al. published in a recent issue of the Journal of Thoracic Disease. Authors describe a rare pericardial neoplasm—primary malignant pericardial mesothelioma (PMPM)—complicated by superior vena cava compression and pericardial constriction (1). They did a commendable job in describing the diagnostic and treatment challenges related to their case. We would however like to highlight the palliative therapeutic approach which remains an extremely important treatment aspect in such cases.